Diseño de un sistema fotovoltaico para el suministro alternativo de energía eléctrica al interior de un vehículo tipo casa-rodante en la ruta turística spondylus o ruta del sol. - Cuenca Benítez, Wilson Alcívar (2018)
The present project describes the design of a photovoltaic system, which was developed as an alternative solution to the electrical energy consumption required by the equipment inside of a type home-rolling vehicle, it is aimed for the touristic activity and travel that runs in the SPONDYLUS or “Ruta del Sol” on the Ecuadorian coast, taking advantage of the solar radiation that because of its geographical location makes its implementation feasible. To reach this, it was first selected electrical equipment of preferential use and taking into account the place where it will be used, in addition, to its energy efficiency and its availability in the market. For this, it was made the estimate for the implementation of an air conditioning and LED lamps, taking into account the climatological characteristics, area of the rolling home, and various factors that determine the appropriate selection of them. Then, the energetic demand of all the equipment was determined for its proper functioning, providing a value of 3566W / h of daily energy. With the help of the page of the "Data Center of Atmospheric Science" NREL-NASA (with average values from 1983 to 2005), it was possible to know the horizontal solar radiation, and with this value and finally applying different methodologies, it was verified the angle of inclination and the solar peak hours HPS in the main tourist places that the "Ruta del Sol" crosses. With the above data it was established that 4 300W photovoltaic panels connected in series-parallel combination, are enough to cover the energy consumption charge of the system. After that, the number of batteries, the charge regulator, the inverter and the conductor cable demanded by the implemented system were calculated. Finally, a technical-economic analysis of the project was carried out in order to establish viability and to know the investment cost needed by the photovoltaic system.